The Impact of Heating Treatment of Black Soldier Fly (BSF) Larvae (Hermentia illunces) on Nutrient Levels - Umar Suryanaga; Binsar Jon Vic (Jurnal Greenation Pertanian dan Perkebunan, 2025)
Black Soldier Fly (BSF) larvae, often called maggots, are a type of fly of the Hermentia illucens species capable of degrading organic waste. These maggots are used as an alternative raw material for poultry or fish feed due to their high animal protein content. Some larval cultivation methods may use poultry manure, which may carry Salmonella sp. bacteria. This study aimed to evaluate the presence of Salmonella sp. and the nutritional content of BSF larvae that had undergone a washing and heating process. Microbiological testing showed that all samples, including the positive control, showed negative results for Salmonella sp. growth, possibly due to low inoculum concentration, suboptimal incubation period, and competition with other Enterobacteriaceae bacteria. Proximate testing showed that washing caused a decrease in nutritional content, while heating treatment, particularly with a microwave at high temperatures (100 grams, 15 minutes), increased nutrient levels and decreased water activity. Low water activity (<0.6) indicates potential for increased shelf life. These results indicate that appropriate thermal treatment can improve the microbiological safety and nutritional quality of BSF larvae as a feed ingredient.